Evaluation of performance characteristics and internal and external training loads in female collegiate beach volleyball players - Bozzini, B. N.; McFadden, B. A.; Scruggs, S. K.; Arent, S. M. (The Journal of Strength and Conditioning Research, 2021)
Although women's beach volleyball is the fastest growing collegiate sport, the training demands and performance characteristics have yet to be determined. The purpose of this study was to evaluate internal and external training loads throughout a competitive season and to quantify the performance characteristics of National Collegiate Athletic Association Division I women's beach volleyball players. Female beach volleyball players (N = 20) were monitored throughout the 6-week competitive season (T1-T6) using integrative global positioning systems (GPS) and heart rate (HR)-monitoring technology, which was individualized based on preseason testing, for the determination of workload metrics. In addition to team data, all variables were analyzed between travel (n = 11, regular match participation) and non-travel (n = 7) squad athletes (p < 0.05). Team performance metrics demonstrated the explosive power emphasis of the sport, with travel squad players exhibiting significantly greater vertical jump and jump velocity abilities than their non-travel counterparts (p < 0.05). Although few time main effects from T1 to T6 were observed for team workload metrics, follow-ups revealed significant time × group interactions for training load (TL), exercise energy expenditure (EEE), total distance covered, and minutes spent in HR zones (HRZ1-Z5) over the season (p < 0.05). Finally, although average workloads were greater in practices than in matches, when accounting for pre-match warm-ups, competition load was greater than practice (p < 0.05). National Collegiate Athletic Association Division I women's beach volleyball is a demanding, explosive power sport characterized by overall large TL and EEE, particularly in-season when athletes compete in 4 matches per weekend. The workloads observed point to the need to assess and manage training loads and fueling requirements to optimize performance and decrease injury risk.